Предмет: Алгебра, автор: melnik210

Упростите выражение,люди добрые

Приложения:

Ответы

Автор ответа: 93931
0
((5k-5) / (k²-1) - k / (k+1)) : (5-k) / (k+1) = ((5k-5) / (k-1)(k+1) - k / (k+1)) :  
(5-k) / (k+1) = ((5k-5) / (k-1)(k+1) - (k²-k) / (k-1)(k+1)) : (5-k) / (k+1) = 
(5k-5-k²+k) / (k-1)(k+1) : (5-k) / (k+1) = (6k-k²-5) / (k-1)(k+1) : (5-k) / (k+1) = 
(6k-k²-5)(k+1) / (k-1)(k+1)(5-k) = (6k-k²-5) / (k-1)(5-k) = (6k-k²-5) /
(5k-k²-5+k) = (6k-k²-5) / (6k-k²-5) = 1.
Похожие вопросы
Предмет: Математика, автор: nikolaidauhashei